A NEW COMBINATION FOR A SUBSPECIES OF RADERMACHERA QUADRIPINNATA (BIGNONIACEAE) - Ian Turner (Research Center for Biology, 2017)
TURNER, I. M. 2017. A new combination for a subspecies of Radermachera quadripinnata (Bignoniaceae). Reinwardtia 16(1): 47 – 48. — The new combination Radermachera quadripinnata subsp. lobbii is made to replace subsp. acuminata as the autonym Radermachera lobbii subsp. lobbii has priority over R. lobbii subsp. acuminata. Lectotypes are designated for Spathodea lobbii Teijsm. & Binn. and Radermachera lobbii subsp. acuminata Steenis.